Translucency of 3D-printed 3Y- and 5Y-doped zirconia - Hetzler, Sebastian; Schmitt, Clemens; Rammelsberg, Peter; Rues, Stefan; Zenthöfer, Andreas (Journal of esthetic and restorative dentistry, 2025)
Objectives To evaluate and compare the translucency of 3D-printed zirconia materials: 3Y tetragonal zirconia polycrystal (3Y-TZP) and 5Y partially stabilized zirconia (5Y-PSZ). Material and Methods 3D-printed 5Y-PSZ and 3Y-TZP materials fabricated using digital light processing (DLP) were investigated. In addition, three zirconia materials made for the milling approach were examined: one 3Y-TZP and two 5Y-PSZ variants. For translucency measurements, samples with a square base of 100 mm2 and five different thicknesses ranging from 0.25 to 1.25 mm (±50 μm tolerance) were produced (n ≥ 5/subgroup). The L*a*b* color coordinates were measured using an experimental setup consisting of a spectroradiometer, an integrating sphere, and a 35-W tungsten lamp. The translucency parameter was calculated using the color difference between white and black backgrounds. The microstructure and grain size were analyzed using scanning electron microscopy. Results Translucency increased with a decrease in thickness, across all materials. Milled materials exhibited higher translucency than 3D-printed counterparts with equivalent yttria content. The 3D-printed 5Y-PSZ and milled 3Y-TZP materials displayed comparable translucencies. Microstructural analysis revealed discrete microporosities in the 3D-printed materials. Conclusions Despite microstructural differences and defects reducing the translucency of 3D-printed zirconia compared to their milled counterparts, 3D-printed 5Y-PSZ demonstrates sufficient optical properties for monolithic restorations in posterior regions.
Vorab veröffentlicht: 09. Dezember 2025
Gesehen am 23.02.2026